Modern state of aquatic biological resources of the Amur River basin and directions of their research - N. V. Kolpakov; D. V. Kotsyuk; V. I. Ostrovsky; N. N. Semenchenko; V. N. Koshelev; A. P. Shmigirilov; E. V. Ostrovskaya; E. I. Barabanshchikov; T. V. Kozlova; S. E. Kulbachny; E. V. Podorozhnyuk; O. V. Vilkina; et al. (Известия ТИНРО)
Current status of aquatic biological resources in the middle and lower parts of the Amur River basin, including Lake Khanka and the Amursky Liman, is assessed. Generally high abundance of the water organisms is noted, but a downward trend is revealed. In 2015–2019, the total annual catch in the basin by Russian fishermen changed between 15.9–69.6 . 103 t (on average 39.1 . 103 t), with the main portions of pacific salmons (31.9 . 103 t, or 81.6 % of total catch) and smelts (5.5 . 103 t, 14.1 %). After the peak in 2016, the salmons abundance in the Amur has decreased, particularly for summer chum salmon and pink salmon, the number of arctic rainbow smelt Osmerus dentex has decreased gradually in the last 3 years. The stocks of freshwater fish are generally stable, with a slight increase for some species. The program of fisheries research «Amur River Fishes» implemented for 2020–2024 includes intensifying of traditional monitoring of the stocks and their biological state, as well as organization of detailed comprehensive studies for key species. Improvement of data quality on status of the main stocks of pacific salmons, smelts, and freshwater fishes is planned, as the basis for fisheries forecasting. Besides, the program conducts quantitative assessment of the main components of the ecosystem (phyto- and zooplankton, macrozoobenthos, and fish) and their dependence on environmental changes. State of food base for the Amur fish will be evaluated, including the feeding of artificially reproduced juveniles of salmons and sturgeons. Results of these studies will allow to improve approaches to regulation of fishery and to promote development of fishery industry toward organization of effective fishery complex in the Amur River basin.